Denyut Nadi Amandemen Kelima UUD 1945 melalui Pelibatan Mahkamah Konstitusi sebagai Prinsip the Guardian of the Constitution - Ahmad Ahmad; Novendri M. Nggilu (Jurnal Konstitusi, 2019)
Perubahan UUD 1945 yang telah dilakukan MPR membuktikan, bahwa ada benturan kepentingan sehingga menjadikan perubahan konstitusi yang ‘tambal sulam’ dan tidak berorientasi kepentingan jangka panjang, serta jauh dari kata memuaskan karena ‘elitis’ dan kurang partisipatif, maka perubahan konstitusi seharusnya tidak dilakukan oleh satu lembaga saja yang dalam hal ini adalah MPR. Oleh karna itu, penting kirannya melibatkan Mahkamah Konstitusi agar tercipta hasil perubahan UUD NRI 1945 yang partisipatif. Penelitian ini bertujuan untuk mengetahui tentang apa urgensi pelibatan mahkamah konstitusi dalam perubahan Undang Undang Dasar Negara Republik Indonesia  Tahun 1945, dan bagaimana prospektif pelibatan mahkamah konstitusi dalam perubahan undang undang dasar  Negara Republik Indonesia  Tahun 1945. Penelitian ini mengunakan Jenis penelitian normatif. Hasil penelitian ini menunjukan bahwa Urgensi pelibatan MK dalam perubahan Undang Undang Dasar di dasarkan pada beberapa hal, antara lain: Pertama, terdapat banyak kelemahan dalam amandemen pertama sampai dengan amandemen ke-empat; Kedua, Eksistensi MPR sebagai lembaga politik; ketiga, Pelakasanaan prinsip Checks and Balance System; Keempat, Perwujudan MK sebagai The Guardian Of Consitution. Bahwa Prospektif pelibatan MK dalam perubahan UUD NRI 1945 adalah dengan menekankan pada political good will dari MPR untuk menyusun Mekanisme perubahan UUD NRI 1945 dengan melibatkan MK sebagai lembaga negara yang memberikan Sertfikasi Konstitusi dari hasil kajian perubahan yang dilakukan oleh Komisi konstitusi sebelum mendapatkan persetujuan dari MPR untuk ditetapkan sebagai hasil perubahan UUD 1945 yang baru. hasil dari mekanisme perubahan konstitusi dengan melibatkan MK ini ditujukan untuk menghasilkan perubahan konstitusi yang bersifat the people of the constitution.The amendments of the 1945 Constitution that the MPR has done proves that there is a conflict of interest that makes constitutional changes ‘patchy' and not oriented to a long term interest and far from satisfying because of 'elitist' and less participatory. Thus, the changes to the constitution should not be carried out by one institution only which in this case is the MPR. Therefore, it is important to involve the Constitutional Court in order to create a participatory change in the 1945 Constitution of the Republic of Indonesia. This study aims to find out about the urgency of involving the Constitutional Court in the amendment of the 1945 Constitution of the Republic of Indonesia, and how prospective the Constitutional Court to involve in the amendment to the 1945 Constitution of the Republic of Indonesia. This study uses a type of normative research and several approaches, namely; law approach (statue approach), comparative approach, and conceptual approach. The results of this study indicate that the urgency of involving the Constitutional Court in amending the Constitution is based on several things, including: First, the weaknesses in the first amendment to the fourth amendment; Second, the existence of the MPR as a political institution; third, the implementation of the Checks and Balance System principle; Fourth, the realization of the Constitutional Court as the Guardian of Constitution. The prospective involvement of the Constitutional Court in the amendment to the 1945 Constitution of the Republic of Indonesia is to emphasize the political goodwill of the MPR to develop a mechanism for amending the 1945 Constitution of the Republic of Indonesia by involving the Constitutional Court as a state institution which provides a review of changes made by the constitution before obtaining approval from the MPR to be determined as a result of the amendment to the new 1945 Constitution. The result of the constitutional change mechanism by involving the Constitutional Court was intended to produce constitutional changes that have the character the people of the constitution.